The effect of FeSO4, nanoscale silver and { Mo72Fe30} cluster on the oxidation of ethylene glycol by H2O2 - S.Yu.. Menshikov; A.N. Malyshev; V.S. Kurmacheva; S.A. Fedorov; M.O. Tonkushina; A.A. Ostroushko (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
The catalytic properties of FeSO4, nanocluster iron-molybdenum polyoxometalate Mo72Fe30 and nanoscale metallic silver in the liquid-phase oxidation of the ethylene glycol aqueous solutions by hydrogen peroxide were studied. O-phenylenediamine was added to the reaction mixtures obtained after oxidation to determine the oxidation products containing the aldehyde group. The polyoxometalate Mo72Fe30 was synthesized by a well-known and widely used in practice two-step method. The colloidal silver solution was obtained using a technique based on the Turkevich method. According to the analysis carried out on a laser particle size analyzer, the majority of the silver particles have a size of about 2 nm. The analysis of unreacted ethylene glycol was carried out by GC-FID. According to the conversion of ethylene glycol, nanoscale metallic silver was found to have the highest activity at approximately the same percentage of catalysts in the initial reaction mixture. At the same time, with the addition of o-phenylenediamine, the presence of compounds with an aldehyde group, whose exit time from the chromatographic column is longer than that of the initial ethylene glycol, was noted among the oxidation products.